Application of BEM to modelling loudspeaker's directivity patterns based on its dynamic behaviour - Skrodzka, E. B.; Sęk, A. P. (Archives of Acoustics, 2001)
This paper is concerned with numerical modelling of directivity patterns of loudspeakers. The Boundary Element Method (BEM) was used. Results of modal analysis served as the boundary conditions for modelling. For a loudspeaker with a planar membrane and a woofer with a quasi-conical paper membrane, the directivity patterns found during modelling were compared to characteristics measured in an anechoic chamber. It was shown that the calculated patterns were similar to those measured in the chamber. In particular, the position of an acoustic axis and value of sound pressure level along the main axis of symmetry was predicted with satisfactory precision. Thus, the relation between vibration and radiation of the loudspeakers was shown.